2008
DOI: 10.1016/j.ijhydene.2008.02.009
|View full text |Cite
|
Sign up to set email alerts
|

In situ X-ray diffraction under H2 of the pseudo-AB2 compounds: YNi3.5Al0.5Mg

Abstract: In situ XRD a b s t r a c tThe hydrogenation and dehydrogenation behaviours of the YNi 3.5 Al 0.5 Mg compound were studied by in situ X-ray diffraction under hydrogen pressure and at room temperature. The changes of (i) the lattice parameters, (ii) the crystallite size and (iii) the lattice strain during the sorption process (i.e. along the PC isotherms) were studied. These results indicate that the crystallite size decreases by a factor of 2. The micro deformations increase at first and then tend to almost ze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Different crystal structures were reported for hydrides of stoichiometric Mg 1.0 RE 1.0 Ni 4 by the different groups, even for the same nominal composition. To our knowledge, the crystal structures of the hydrides for Mg 1.0 Gd 1.0 Ni 4– x Al x , and Mg 1.0 Y 1.0 Ni 3.5 Al 0.5 were reported to have a cubic MgCu 4 Sn structure, but those for Mg 1.0 Nd 1.0 Ni 4 and Mg 1.0 Y 1.0 Ni 4 were reported to have an orthorhombic structure. For Mg 1.0 La 1.0 Ni 4 , both hydride crystal structures were reported .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Different crystal structures were reported for hydrides of stoichiometric Mg 1.0 RE 1.0 Ni 4 by the different groups, even for the same nominal composition. To our knowledge, the crystal structures of the hydrides for Mg 1.0 Gd 1.0 Ni 4– x Al x , and Mg 1.0 Y 1.0 Ni 3.5 Al 0.5 were reported to have a cubic MgCu 4 Sn structure, but those for Mg 1.0 Nd 1.0 Ni 4 and Mg 1.0 Y 1.0 Ni 4 were reported to have an orthorhombic structure. For Mg 1.0 La 1.0 Ni 4 , both hydride crystal structures were reported .…”
Section: Discussionmentioning
confidence: 82%
“…The hydrogen storage properties for Mg 1.0 RE 1.0 Ni 4 (RE = Y, La, Ce, Nd, or Gd) have been reported by several groups. Among them, only Mg 1.0 La 1.0 Ni 4 has been known to absorb hydrogen around 1.0 H/M through two plateaus in a similar way to Mg 1.0 Pr 1.0 Ni 4 ; , the reported hydrogen capacities for the other Mg 1.0 RE 1.0 Ni 4 compounds were around 0.6–0.7 H/M. The dependence of the ratio of Mg and RE on hydrogen storage properties which we found in Mg 2– x Pr x Ni 4 has not previously been reported.…”
Section: Introductionmentioning
confidence: 87%
“…The hydrogenation properties and the crystal structures of the hydrides have been reported for several Mg 1.0 RE 1.0 Ni 4 alloys with C15b structures. Different crystal structures of the hydrides, Mg 1.0 RE 1.0 Ni 4 H ∼4 , were reported by different groups, even though they all prepared hydrides with the same stoichiometric alloy composition. To our knowledge, hydrides with C15b structures were reported for Mg 1.0 La 1.0 Ni 4 , Mg 1.0 Gd 1.0 Ni 4‑ x Al x , and Mg 1.0 Y 1.0 Ni 3.5 Al 0.5 , while orthorhombic hydrides were reported for Mg 1.0 La 1.0 Ni 4 , Mg 1.0 Nd 1.0 Ni 4 , and Mg 1.0 Y 1.0 Ni 4 . On the other hand, the theoretical calculation for Y 1.0 Mg 1.0 Ni 4 performed by Pregent and Gupta showed that Y 1.0 Mg 1.0 Ni 4 H 4 is more stable with an orthorhombic structure than with a C15b structure.…”
Section: Discussionmentioning
confidence: 85%
“…The hydrogenation properties of the related Mg 1.0 RE 1.0 Ni 4 materials with RE = Y, La, Ce, Nd, and Gd have also been reported. Although most of the reported hydrides have similar hydrogen contents of ∼0.6 H/M, two types of crystal structures, the C15b and orthorhombic structures, have been reported. The difference in the crystal structure cannot be directly explained by the choice of rare earth element or composition; for example, two different structures were reported even for the same composition of Mg 1.0 RE 1.0 Ni 4 . This crystal structure difference may arise from the different synthesis methods, such as ball-milling or melting, and/or a small deviation from the stoichiometric composition. The latter hypothesis is supported by the clear dependence of the crystal structure on the ratio of Mg to Pr found in Mg 2– x Pr x Ni 4 , as described above …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, to overcome the low hydrogen weight density, Mg containing hydrogen-absorbing alloys have been investigated because Mg is a light metal element. Chotard et al found that Mg 1.0 La 1.0 Ni 4 absorbed hydrogen up to ∼1.0 H/M (H/M: ratio of the number of hydrogen and metal atoms) with two distinct plateaus on the pressure–composition ( P – C ) isotherms, although most reports indicate Mg 1.0 RE 1.0 Ni 4 absorbed hydrogen only up to ∼0.7 H/M with one plateau. We found the dependence of the hydrogenation properties and the crystal structure of the hydride on the Mg/RE ratio in Mg 2– x RE x Ni 4 . The compound with x = 1.0 forms two different hydride phases, an orthorhombic Mg 1.0 RE 1.0 Ni 4 H ∼4 and a C15b Mg 1.0 RE 1.0 Ni 4 H –6 ; those with x < 1.0 have only C15b Mg 2‑ x RE x Ni 4 H ∼3.6 , and those with x > 1.0 transform to amorphous hydride with or without formation of orthorhombic hydride. This indicates that the metal lattice of Mg 2– x RE x Ni 4 with x < 1.0 expanded isotropically while that of Mg 2‑ x RE x Ni 4 with x ≥ 1.0 expanded anisotropically.…”
Section: Introductionmentioning
confidence: 99%